Value Creation From a Decentralized Car Ledger - Bauer, Ingrid; Zavolokina, Liudmila; Leisibach, Fabian; Schwabe, Gerhard (Frontiers in Blockchain, 2020)
Blockchain technology is expected to create a variety of new opportunities for businesses. Yet, little is known about how the technology actually enables to create value and how companies will be able to exploit true business value. However, without a clear understanding of the value creation potential from the technology, and corresponding adaption of business practices, the realization of value is doomed to failure. Hence, we contribute to this gap by exploring and explicating the specificities of value creation from blockchain in the ecosystem of a car. In the course of an exploratory case study analysis, over a time period of 2 years, we conducted three iterations of interviews and workshops with industry and blockchain experts from five diverse stakeholder groups. In brief, we provide early evidence that (1) blockchain enables value creation through: Distributed Product Innovation, Shared Operational Efficiency, and Controlled Customer Intimacy. Furthermore, we discuss our learnings for businesses in other domains aiming to leverage value from blockchain technology. We do so, by deriving guidelines for each blockchain value discipline. Furthermore, we give recommendations on how blockchain projects in ecosystems should approach multiple blockchain value potentials.